Avaliação da percepção de periodontistas, protesistas, ortodontistas e leigos sobre parâmetros periodontais relacionados à estética do sorriso - Barreto, Alessandra Oliveira (2009)
The concept of facial esthetics has been increasingly diffused, being of interest to both the general public and the surgeon-dentists. However the difficult standardization and high variability in parameters aesthetic existing in the literature result in a huge difference of opinions between professionals and layperson. In this way, objective of this research was to evaluate the perception of periodontistas, protesistas, orthodontists and layperson about aesthetics smile. The sample included 30 periodontistas, 30 protesistas, 31 orthodontists and 37 layperson. The data collection was performed through an interview indirect, by the site, which had fifteen photos to be assessed by the participants. Each photograph was intentionally modified, with four increments 1mm for each amendment, in the program Adobe Photoshop CS2 version 9.0, adding-four aesthetic alterations: exposure gingival, recession gingival, absence of papilla and contour gingival. The smile for periodontistas, 3mm for orthodontists and laity and 4mm for protesistas. And changes in recession gingival, have undertaken the aesthetics of smiling from 2mm in accordance with the periodontistas and protesistas and 4mm for orthodontists and lay people. The end of the research was possible to conclude that the perception of periodontistas, protesistas, orthodontists and layperson are different in relation to aesthetics smile, and that among the changes in the research evaluated the papilla and recession have undertaken the aesthetics of smile